Pengembangan Teknologi E-Marketplace Hasil Bumi di Desa Tumbang Manjul - Dendi Sugito; Lukman Bachtiar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The Tumbang Manjul community is a resident in remote areas, located in the Seruyan Regency, Seruyan Hulu District with abundant natural resources. With the efforts carried out by the community, the business has a serious enough problem to pay attention to, seeing it is less than optimal, it is necessary to have a solution, so that consumers from outside the region can also review the produce from the business in the Tumbang Manjul Community. With the existence of an E-marketplace information system, marketing carried out by sellers can reach a wider area, especially Central Kalimantan, because buyers who come can come from various regions further afield